ANALYSIS THE IMPACT OF HALAL SUPPLY CHAIN ON ENVIRONMENTAL AND SOCIAL SUSTAINABILITY - Kuncorosidi Kuncorosidi; Heru Setiawan; Devi Delviyani (JABI (Journal of Accounting and Business Issues), 2024)
Global awareness of climate change and its impacts has increased in recent years. Movements like "Fridays for Future" started by Greta Thunberg have sparked mass climate action worldwide, pushing governments and companies to take concrete action to reduce greenhouse gas emissions. The problem of plastic pollution is becoming more prominent, with many countries and companies committing to reduce the use of single-use plastic. Research Methods The research method in this research uses a systematic literature review study approach, this methodological procedure was developed to identify references with specific topic relevance in the bibliographic database of scientific journals that have been determined (Campbel 2010 in Ferenhof 2014). The analysis results show that Halal is reflected in Halal Supply Chain Management, while Green Supply Chain Management reflects "thoyy?b?n" (good) in the environment. The two concepts become one unit in "halal?n thoyy?b?n". So the results of research with the application of environmentally friendly concepts in the supply chain of the halal industry provide additional positive impacts on three aspects, namely. Financial, Environmental, and Social.